2008
DOI: 10.1084/jem2053oia8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of “self” engulfment through deactivation of myosin-II at the phagocytic synapse between human cells

Abstract: (2008). Inhibition of "self " engulfment through deactivation of myosin-II at the phagocytic synapse between human cells. Retrieved from http://repository.upenn.edu/cbe_papers/108Inhibition of "self " engulfment through deactivation of myosin-II at the phagocytic synapse between human cells AbstractPhagocytosis of foreign cells or particles by macrophages is a rapid process that is inefficient when faced with "self " cells that display CD47-although signaling mechanisms in self-recognition have remained largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 40 publications
5
88
0
1
Order By: Relevance
“…RBC from mice as well as sheep respectively show weak to no binding to this recombinant hSIRPα when compared to human RBCs (Figure 1A). Based on the lack of sheep RBC interactions with soluble hSIRPα, human macrophages would be expected to phagocytose IgG-opsonized sheep RBC – which is indeed commonly reported in studies of Fcγ receptor mediated phagocytosis [18[19[20]. RBC membranes are nonetheless complex, with many additional differences between species: for example, CD47 on human RBCs is less mobile than on mouse RBCs in part due to human CD47's association with the species-specific Rh complex [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RBC from mice as well as sheep respectively show weak to no binding to this recombinant hSIRPα when compared to human RBCs (Figure 1A). Based on the lack of sheep RBC interactions with soluble hSIRPα, human macrophages would be expected to phagocytose IgG-opsonized sheep RBC – which is indeed commonly reported in studies of Fcγ receptor mediated phagocytosis [18[19[20]. RBC membranes are nonetheless complex, with many additional differences between species: for example, CD47 on human RBCs is less mobile than on mouse RBCs in part due to human CD47's association with the species-specific Rh complex [24].…”
Section: Resultsmentioning
confidence: 99%
“…Based on this divergence, human macrophages might be expected to engulf opsonized sheep RBCs – an expectation borne out by many prior studies using sheep-RBCs as targets for human macrophages in phagocytosis (e.g. [18[19[20]). In addition to the recognition of SIRPα and CD47 between species, there exists considerable polymorphism in SIRPα between mouse strains [21] and between humans [2]; indeed, from a very limited but worldwide study of 37 human haplotypes, 10 variants of SIRPα's ~100 amino acid N-terminal domain were reported.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of SIRPα and that of CD47‐SIRPα interactions in RBC phagocytosis and clearance in vivo was confirmed using mice with a mutant SIRPα receptor lacking the cytoplasmic tail . Further mechanistic studies implicated that binding of CD47 to SIRPα leads to an RBC phagocytosis‐associated deactivation of myosin IIA, which is an important contributor of phagocytosis because of its participation in macrophage actino‐myosin contraction . CD47‐SIRPα interactions also suppress the clearance by macrophages of antibody‐ or complement‐ opsonized erythrocytes, through Fcγ‐ or complement‐ receptors on macrophages, and this could be relevant in the context of autoimmune hemolytic anemia (AIHA) …”
Section: Cd47‐sirpα Interactions As An Immune Checkpoint In Cancermentioning
confidence: 86%
“…Recently, we showed that the polymerized state of actin (i.e., actin elongation) in adherent macrophages correlated with the biocompatibility of surfaces 38. Specifically, macrophages showed a significantly reduced affinity for polymeric surfaces modified with recombinant CD47, a ubiquitously expressed transmembrane protein that reduces the polymerized state of actin through signaling mechanisms mediated by its cognate receptor, Signal Regulatory Protein alpha, or SIRPα 50. Second, 3D quantitative analysis of cell morphology indicates that macrophage surface area and volume as well as spreading behavior depend on surface type.…”
Section: Discussionmentioning
confidence: 99%